KH. AHMAD AZHAR BASYIR, MA.: PROTOTIPE ULAMA-INTELEKTUAL MUHAMMADIYAH - Jinan, Mutohharun (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2014)
Kyai Haji Bashir Ahmad Azhar, MA is known as a scholar-intellectual who once owned Muhammadiyah. He grew up in communities that hold on religious values, in Kauman. Throughout his life was spent in education and da?wah. Educated in boarding schools and formal education at home and abroad. His intelectual career showed through his profession as a lecturer and leader of Muhammadiyah organisation. His thoughts a reference to address the various problems of the people. His thinking is outlined in a number of books, including the field of jurisprudence, philosophy of Islamic law and Islamic economics. His position as chairman of Muhammadiyah  marks the transition process from the clerical leadership to intellectual models.